Can microRNA become next-generation tools in molecular diagnostics and therapeutics? A systematic review - Vandana Saini (Egyptian Journal of Medical Human Genetics, 2021)
Abstract Background MicroRNAs (miRNAs) represent a novel class of single-stranded RNA molecules of 18–22 nucleotides that serve as powerful tools in the regulation of gene expression. They are important regulatory molecules in several biological processes. Main body Alteration in the expression profiles of miRNAs have been found in several diseases. It is anticipated that miRNA expression profiling can become a novel diagnostic tool in the future. Hence, this review evaluates the implications of miRNAs in various diseases and the recent advances in miRNA expression level detection and their target identification. A systematic approach to review existing literature available on databases such as Medline, PubMed, and EMBASE was conducted to have a better understanding of mechanisms mediating miRNA-dependent gene regulation and their role as diagnostic markers and therapeutic agents. Conclusion A clear understanding of the complex multilevel regulation of miRNA expression is a prerequisite to explicate the origin of a wide variety of diseases. It is understandable that miRNAs offer potential targets both in diagnostics and therapeutics of a multitude of diseases. The inclusion of specific miRNA expression profiles as biomarkers may lead to crucial advancements in facilitating disease diagnosis and classification, monitoring its prognosis, and treatment. However, standardization of methods has a pivotal role in the success of extensive use of miRNA expression profiling in routine clinical settings.